Ethnobotanical Study of Medicinal Plants for the Circulatory System in Kaloy Village, Tamiang Hulu Subdistrict, Aceh Tamiang Regency - Mustaqilla, Safira; Aththorick, T Alief; Nurwahyuni, Isnaini (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2025)
This study aims to document the traditional knowledge of the local community in Kaloy Village, Tamiang Hulu Subdistrict, Aceh Tamiang Regency regarding the use of medicinal plants for treating circulatory system disorders. The methods used include in-depth interviews, direct observation, and documentation involving 90 respondents from various age groups and two key informants. The results show that the community's trust in medicinal plants remains high, particularly among individuals aged over 50. A total of 10 plant species were identified and used to treat diseases such as hypertension, high cholesterol, anemia, stroke, and diabetes. The most commonly utilized plant parts were leaves and rhizomes, with traditional processing methods such as boiling, pounding, and chewing. The study also calculated the Index of Cultural Significance (ICS) to assess the cultural importance of each species in the community. These findings indicate that ethnobotanical knowledge is still well preserved among the older generation but is beginning to decline among the youth.